A self-regulated gradient interphase for dendrite-free solid-state Li batteries. Issue 3 (16th February 2022) - Wang, Tengrui; Duan, Jian; Zhang, Bao; Luo, Wei; Ji, Xiao; Xu, Henghui; Huang, Ying; Huang, Liqiang; Song, Zhenyou; Wen, Jiayun; Wang, Chunsheng; Huang, Yunhui; et al.
Abstract : A functional gradient lithium anode (FGLA), where a LiF-rich layer faces garnet side and gradually changes to a LiAl-rich layer facing Li side, effectively prevents solid-state electrolytes from dendrite penetration at high current densities. Abstract : Solid-state Li metal batteries (SSLMBs) have emerged as an important energy storage technology that offers the possibility of both high energy density and safety by combining a Li metal anode (LMA), a high-capacity cathode and a nonflammable solid-state electrolyte (SSE). However, the major challenges of poor LMA/SSE interface wetting and the easy growth of Li dendrites in SSEs remain unsolved. Here, we have addressed these challenges by using a functional gradient Li anode (FGLA), which is formed through a self-regulated reaction between molten Li and AlF3 . A composition gradient of Li–LiAl–LiF is spontaneously formed from the reaction of molten Li with AlF3 due to the large difference in interfacial energy between Li/LiAl and Li/LiF, where the LiAl reduces the interface resistance and LiF suppresses Li dendrites. The FGLA not only dramatically reduces the resistance at the FGLA/Li6.5 La3 Zr1.5 Ta0.5 O12 (LLZTO) garnet SSE interface to ∼1 Ω cm −2, but also largely increases the critical current density (CCD) to over 3.0 mA cm −2 at room temperature. Moreover, the full cells paired with LiNi0.5 Co0.2 Mn0.3 O2, sulfur and thick LiFePO4 cathodes (∼2.8 mA h cm −2 ) also show excellent cycling performances. The FGLA design provides a great opportunity for safe and high-energy SSLMBs.